Magnesium status in Olympic & Paralympic athletes compared with a sedentary population and validation of a FFQ as an assessment tool for dietary magnesium intake - Killer, S. C.; Brown, R. A.; Collins, A. L. (International Journal of Sport Nutrition and Exercise Metabolism, 2017)
Magnesium (Mg) is an essential mineral involved in over 350 enzymatic reactions within the human body and plays a fundamental role in electrolyte balance, cellular growth and glucose homeostasis. Literature suggests Mg deficiencies may be prevalent within athletic populations, but it is not clear whether this is due to reduced dietary intakes or increased utilisation of Mg due to high levels of physical activity. The aims of the study were two-fold. Firstly to validate a food frequency questionnaire (FFQ) against a 4-day diet diary and to compare intakes with blood samples for its potential to predict status. Secondly, to compare dietary intakes and plasma Mg status in elite athletes compared with a sedentary population. Thirty-eight individuals participated in the study; 24 elite athletes (Olympic & Paralympic track and field) and 14 non-athletes (age 18-30 y). Participants completed a FFQ and provided a venous blood sample. In addition, the non-athlete group completed a 4-day diet diary. Analysis of plasma Mg was carried out using ICP-MS. Plasma Mg status was lower in elite athletes compared with non-athletes (1.2 ± 0.1 vs 1.4 ± 0.3 mg/dL; p=0.03), despite similar intakes of dietary Mg (431 ± 140 vs 458 ± 165 mg; p>0.05). Self-reported Mg intake assessed by FFQ was correlated to intakes from diet diaries from the non-athlete group (p<0.01), suggesting FFQ to be a valid tool for dietary assessment. Dietary intakes were not correlated with plasma Mg status. Lower plasma Mg levels in athletes compared with non-athletes suggest enhanced nutrient demands during exercise may be causing a transient shift of Mg from the plasma to sites of metabolic demand. Red blood cell (RBC) analysis may provide greater insight into overall Mg status in athletic populations, despite plasma analysis currently portrayed as the gold standard measurement for clinical investigations. The lack of correlation between Mg intake and status was likely the result of the transient nature of plasma Mg analysis. Intestinal absorption and excretion of Mg is critical in the maintenance of plasma status, therefore high consumption does not necessarily result in elevated plasma levels. Repeated analysis of Mg across a season is important for maintaining health and performance in athletes and should be assessed in RBCs where possible.